Genetics of yield and yield-contributing traits in Indian mustard (Brassica juncea) - SINGH, V V; CHAUHAN, J S; RAM, BHAGIRATH; SINGH, MAHARAJ; MEENA, M L (The Indian Journal of Agricultural Sciences, 2012)
Generation mean analysis was performed using two crosses Maya × BPR 543-2 and BPR 543-2 × BPR 2 to study the nature and magnitude of gene effects for yield and its component characters in Indian mustard [Brassica juncea (L.) Czern & Coss]. The F1, F2, BC1 and BC2 of these crosses alongwith P1 and P2 were studied for fourteen morphological traits. Additive × dominance (j) type interaction was observed for plant height, main shoot length, primary branches/plant and seed yield/plant and (h) gene effect was found to be predominant in the expression of these traits. The cross BPR 543-2 × BPR 2 showed (d) and (j) effects for main shoot length, a simple additive-dominance model being adequate for the other cross to have a positive shift in the expression of the phenotypic means, it is essential to harness both the additive and non- additive gene effects prevalent in the main shoot length strength. The seed yield/plant in the cross Maya × BPR 543-2 showed (d), (h) and additive × additive (i) type gene interaction indicate, that this trait is under the control of both fixable and non-fixable gene effects. The additive × additive (i) type gene interaction and duplicate epistasis seen in this trait suggest the possibilities of obtaining transgressive segregants in later generations. The study revealed the importance of both additive and non-additive types of gene interaction for all the traits studied.